Textual Function in English Morphology Online Classroom - Tri Indah Rezeki (English Teaching and Linguistics Journal (ETLiJ), 2020)
A clause is a unit of message.  As a message a clause divide into two parts, namely the Theme and Rheme. The aim of this present research is to analyze textual function in English Morphology online classroom. The scopes of this research are analysis of textual function in English Morphology online classroom, classification of Theme in English Morphology online classroom and kinds of Theme dominantly used in English online classroom. The researcher applied descriptive qualitative research to collect the data from the discourse of the lecturer and the students in English Morphology online classroom at Universitas Islam Negeri Sumatera Utara. The data was obtained into three phases namely separated the text into clauses, analyzed each clause in terms of the textual function (i. e Theme and Rheme) and classified elements of the Themes (into the four types of Theme). The data indicated that the lecturer and the students used textual function in their discourse in online classroom. Kinds of textual function they used were 7 Unmarked Simple Theme (UST), 3 Unmarked Multiple Theme (UMT), 16 Marked Simple Theme (MST), and 2 Marked Multiple Theme (MMT). In this case, MST was dominant used by the leacturer and the students in English online classroom.